2021
DOI: 10.1097/md.0000000000027315
|View full text |Cite
|
Sign up to set email alerts
|

Volunteer activity and depression among the elderly in China

Abstract: Participation in volunteer activity has positive effects on health among elderly. Few studies have investigated the association between volunteer activity and depression among Chinese elderly. This study aimed to examine the association between volunteer activity and depression among the elderly in China regarding rural–urban differences. Totally 8255 subjects from the 2015 China Health and Retirement Longitudinal Study were selected in this study. Depression was assessed by 10-item Center for Epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Helping activities have no significant effect on the risk of depression in the elderly, which is in line with the previous study (12,18). Some studies have found that there is a negative association between formal volunteer activity and depression among urban elderly, while there is a positive association between caring for a sick or disabled adult and depression among both urban and rural elderly (36). However, this is not a contradiction.…”
Section: Discussionmentioning
confidence: 98%
“…Helping activities have no significant effect on the risk of depression in the elderly, which is in line with the previous study (12,18). Some studies have found that there is a negative association between formal volunteer activity and depression among urban elderly, while there is a positive association between caring for a sick or disabled adult and depression among both urban and rural elderly (36). However, this is not a contradiction.…”
Section: Discussionmentioning
confidence: 98%
“…Many past studies have found that participating in volunteering is related to lower levels of depressive symptoms 19,64 . However, participating in volunteering activities or community meetings was not significantly related to depressive symptoms.…”
Section: Discussionmentioning
confidence: 88%
“…63 Many past studies have found that participating in volunteering is related to lower levels of depressive symptoms. 19,64 However, participating in volunteering activities or community meetings was not significantly related to depressive symptoms. The reduction in depressive symptoms may be related to the intensity and quality of participation, but such data were unavailable in the IFLS.…”
Section: Structural Social Capital and Emotional Wellbeingmentioning
confidence: 92%
“…The social support investigated in our study included volunteering, grandparenting, and community and religious participation. Recent studies have indicated that engagement in voluntary work, community activities and leisure activities is associated with a reduced risk of depressive symptoms in older adults (37)(38)(39)(40). Older adults with higher community participation have often been found to have better physical functioning, improved subjective well-being and life satisfaction, decreased loneliness and a lower level of depression (41).…”
Section: Discussionmentioning
confidence: 99%